Challenge of governance in Nigeria: lessons from Muhammad Bello’s "principle of leadership" (2017)
Nigeria is confronted with the challenge of leadership which often led to polity debacle and frustration among the masses who are always at the receiving end of governance deficits. Previous studies on leadership have focused on the concept and theories of leadership, and governance in Nigeria with little attention to application of the principles of leadership of Muhammad Bello to governance in Nigeria. Hence, this paper examines the contribution of Muhammad Bello to governance and investigates the possibility of applying his principle on leadership to the body polity in Nigeria with a view of solving the leadership deficit confronting the Country. Data for the paper was sourced through content analysis of literature. The paper discovered that although Nigeria is a multireligious state, Muhammad Bello's principles can still be applied to the Country given the principles of universality contained in it. The paper concluded by recommending that the leadership principles enumerated by Muhammad Bello should form part of school curriculum at all levels and be taught to prospective political office holders in the Country through the instrumentality of the Nigerian Institute of Democratic Studies.